2019
DOI: 10.31234/osf.io/2ubtx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mate Preferences in Three Muslim-Majority Countries: Sex Differences and Personality Correlates

Abstract: Cross-cultural research on long-term mate preferences in Muslim-majority countries is scarce. The research described here aims to examine the KASER (kindness/dependability, attractiveness/sexuality, status/resources, education/intelligence, and religiosity/chastity) model of mate preferences in Iran, Pakistan, and Turkey (N = 1,089). We examined structural validity, measurement invariance between men and women, sex differences, cultural differences, and Big Five personality correlates of these dimensions of ma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Some studies have provided evidence of change in preferences over time (Souza et al, 2016). Studies utilizing personality traits have provided evidence that people prefer traits that are associated to their own traits even in more traditionalistic societies such as Islamic countries (Atari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have provided evidence of change in preferences over time (Souza et al, 2016). Studies utilizing personality traits have provided evidence that people prefer traits that are associated to their own traits even in more traditionalistic societies such as Islamic countries (Atari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-cultural study of the differences between Chinese and American mate selection preferences, it was found that wealth factors are predominant in Chinese mate selection preferences, while in the United States, honesty and trustworthiness are attached more importance to gradually [ 32 ]. Based on similar cultural backgrounds, differences in mate selection preferences have also been found among other countries; kindness, dependence, religion, and chastity are only positively related in Iran, according to a study on mate preferences in three Muslim-majority countries: Iran, Pakistan and Turkey [ 33 ]. A recent study on mate preferences in gender-equitable countries indicated that men and women have almost identical preferences for earning capacity [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extroverts are found to be happier than introverts, particularly because social engagement plays a positive role in making a person satisfied with life-condition regardless of the personality ( Vella-Brodrick et al., 2009 ). While it is argued that monogamy has no monopoly on health, happiness, sexual or marital satisfaction ( Cox et al., 2021 ), choosing a long-term romantic partner is a major decision because it affects a person's life in many ways ( Atari et al., 2020 ). Proper mate choices are found to be associated with mental health ( Waynforth, 2007 ), social attitude ( Alford et al., 2011 ), and subjective well-being ( Kim and Hatfield, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studying mate selection has become not only an intrinsically fascinating topic but also an important theme to address the dramatic cultural evolution of human mating strategy ( Buss and Schmitt, 2019 ). Many studies ( Atari et al., 2020 ; Buss, 1989 ; Buss and Barnes, 1986 ; Shackelford et al., 2005 ) report mate preferences by sex differences, and some studies relate their findings to personality differences ( Botwin et al., 1997 ; Keldal, 2020 ). Indeed, universal sex differences have been found in mate preferences; women prioritize greater financial prospects and men emphasize physical attractiveness ( Buss, 1989 ; Walter et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%